Acceptability of Partner Violence in 51 Societies: The Role of Sexism and Attitudes Toward Violence in Social Relationships. (March 2017) - Herrero, Juan; Rodríguez, Francisco J.; Torres, Andrea
Sexist attitudes have been claimed to play an important role in acceptability of intimate partner violence (IPV). Empirical evidence suggests that sexist individuals are also more accepting of violence in social relationships than non-sexist individuals. Results from multilevel regression models of data from 72, 730 respondents of 51 countries around the world showed that (a) both sexism and acceptability of general violence in social relationships were positively related to acceptability of IPV and (b) the highest levels of acceptability of IPV were found among those sexist individuals who also present positive attitudes toward the use of violence in social relationships.